A NEW APPROACH TO THE PROBLEM OF CREATING THE SYSTEM OF FLIGHT SAFETY MANAGEMENT IN STATE AVIATION OF RF - B. I. Bachkalo; R. Е. Irmaliev (Научный вестник МГТУ ГА, 2016)
This article considers the drawbacks weaknesses of the current system of flight safety, a new approach to organize this system, which is based on creating two control loops - a control loop managing flight safety.